Correlation and Influencing Factors Between Laryngopharyngeal Reflux Disease and Sleep Status in Patients - Liu, Yue; Wu, Jian; Xiao, Feng; Gu, Xiaofeng; Ji, Li (Frontiers in Surgery, 2022)
Objective To observe the correlation between laryngopharyngeal reflux disease (LPRD) and patients' sleep status, and to explore the related factors of LPRD. Methods Four hundred and sixteen patients who visited the otorhinolaryngology clinic in our hospital from June 2019 to June 2021 were selected as the research subjects. According to the scale of reflux symptom index, the subjects were divided into a patients group (120 patients) with an the reflux symptom index (RSI) > 13 and a control group (296 patients) with an RSI ≤ 13 according to the RSI scale score. General patient information was collected. The sleep state and emotional state of patients in the two groups were evaluated, and the related influencing factors for LPRD were also evaluated. The correlation between sleep state and depression in LPRD patients was analyzed. Results Four hundred and sixteen patients were divided into patients group and control group according to RSI score, the ratio of the two groups was 1:2.47. In the patients group, the common symptoms of RSI score and the top three of the total score were as follows: Foreign body sensation in throat in 112 patients, 438 points; Keep voice clear in 108 patients, 381 points; Excessive phlegm or nasal discharge reflux in 101 patients, 348 points. The PSQI and HADS scores in the patients group were higher than those in the control group (t = 19.990, 13.007, 14.690, P all <0.001). Logistic regression analysis showed that high-fat diet and high PSQI score were the risk factors for the development of LPRD (P = 0.012, P = 0.007). According to the PSQI score, the patients in the patients group were divided into 35 patients with abnormal PSQI score, 85 patients with normal PSQI score, and the HADS scores of those with abnormal PSQI score were all lower than those with normal PSQI score (P > 0.05). The PSQI score of the patients in the patients group was positively correlated with the HADS score (r = 0.714, P = 0.013). Conclusion Sleep disorder may lead to the occurrence or aggravation of anxiety and depression in patients with LPRD, and it is an independent risk factor for the development of LPRD. Clinical attention to the treatment of sleep disorders in patients with LPRD may be conducive to improving the efficacy of LPRD.